MDSA, MULTI DECISION SCHEDULING ALGORITHM FOR UE ENERGY POWER SAVING ON MOBILE NETWORKS - Luan Ruci; Luan Karcanaj (European Scientific Journal, ESJ, 2013)
﻿Nowadays general different kind of recurrent network applications on mobile phones are like: news feed, podcast and e-mail which mostly run in the background and are a significant source of power consumption on battery limited mobile phones. Theory of scheduling such applications by prioritizing and evaluating step by step based on many conditions (or even parameters, timers) like radio network parameters, timeout values, coverage conditions or RSSI, switching between 2G and 3G on packet data, etc is our main focus on this paper. Cellular network providers typically try to control these timeout values, though some mobile devices use a technique called fast dormancy in order to reduce the time out duration which mostly results in huge power consumption for end user. The duration of this timeout, which ranges from a few seconds to ten seconds or more, is chosen to balance the cost of signaling for resource allocation to move a radio into active state (and the resulting latency and energy costs on the device) and the wasted resources due to maintaining a radio unnecessarily in active state. We also illustrate the significant energy savings that can be achieved via scheduling of recurrent mobile phone applications considering some network parameters, conditions and also user activity time (clock time) and phone battery condition as an add. These kinds of applications such as email syncing, facebook or photo uploads can defer communication, up to a point, without sacrificing service and user perception. Other applications such as on-demand streaming can prefetch content in anticipation of future need and this will not be considered for now on our study. The other very common service for mobile users is voice and by transmitting data when a call is active brings an extension on mobile phones battery life.